KAJIAN PENGGUNAAN KAPASITAS TRAKTOR KOMATSU D85E- SS DALAM UPAYA PENINGKATAN PRODUKTIVITAS PENYARADAN - Wesman Endom; Sukanda Sukanda (Jurnal Penelitian Hasil Hutan, 1995)
This research was aiming at indentifying the tractor skidding capasity in logging operation in the natural production forest. The tractor observed was Komatsu D85E-SS. and in this study the specific gravity of 0.8 for all species was assumed.The results shows that the capasity of skidding was about 14. 7 ton or equal to 18, 40 m log. However, it was found that from 52 observations, 8% were done under the 20% capacity, 42% of the skidding were done under 21-40% capacity, 25% were done under 40% capacity and 8% were done by winching. .Those figures indicate that the skidder capacity has not yet fully utilized. Therefore, the possibility to increase the volume of skidding is widely open, meaning that the logging wastes can be overcome by skidding those above clear bole parts together with the main log.The cost of skidding per m3 compared with 20 years ago was found to be three times higher. The cost skidding per m3 was about Rp. 3225,- at the averege distance of 3,16 hm.